Food availability modulates the combined effects of ocean acidification and warming on fish growth - Cominassi, Louise (Sci Rep, 2020)
When organisms are unable to feed ad libitum they may be more susceptible to negative effects of environmental stressors such as ocean acidification and warming (OAW). We reared sea bass (Dicentrarchus labrax) at 15 or 20 °C and at ambient or high PCO(2) (650 versus 1750 µatm PCO(2); pH = 8.1 or 7.6) at ad libitum feeding and observed no discernible effect of PCO(2) on the size-at-age of juveniles after 277 (20 °C) and 367 (15 °C) days. Feeding trials were then conducted including a restricted ration (25% ad libitum). At 15 °C, growth rate increased with ration but was unaffected by PCO(2.) At 20 °C, acidification and warming acted antagonistically and low feeding level enhanced PCO(2) effects. Differences in growth were not merely a consequence of lower food intake but also linked to changes in digestive efficiency. The specific activity of digestive enzymes (amylase, trypsin, phosphatase alkaline and aminopeptidase N) at 20 °C was lower at the higher PCO(2) level. Our study highlights the importance of incorporating restricted feeding into experimental designs examining OAW and suggests that ad libitum feeding used in the majority of the studies to date may not have been suitable to detect impacts of ecological significance.